The Structural Efficiency Of Tapered Steel Section With Perforation Under Lateral Torsional Buckling Behaviour - Lim, Cheng Kuan (Universiti Sains Malaysia, 2018)
Tapered beams have the ability to resist a maximum stress at a single location while the stresses are considerably lower at in the rest of the member and therefore it could have a higher structural efficiency compared to conventional beams. It could also satisfy functional requirements while reducing weight and cost in many fields of civil construction. Perforation in steel section also eases the integration of Mechanical and Electrical (M&E) services such as ventilation pipes and electrical cables within the structural depths of the beam. In this research, the structural efficiency of tapered steel section with perforation under lateral torsional buckling behaviour were investigated. A total of 81 models were analysed using LUSAS software and five variables that are being investigated are size of opening, shape of opening, opening layout, tapering ratio and flange and web thickness. Buckling moment is obtained from the results in LUSAS while self-weight and structural efficiency is calculated manually. From the results, opening size of 0.75D has the highest structural efficiency although it can withstand a smaller buckling load. This is due to its lower self-weight compared to other opening size. Square opening shape also has the highest structural efficiency compared to circular opening and diamond opening. The percentage increase in structural efficiency of square opening shape of 0.75D is the highest at 3.07%. Circular opening shape of 0.75D with Open-Open-Open opening layout has the highest percentage increase in structural efficiency which is 2.37%. Tapering ratio of 0.3 is the most structurally efficient and the percentage increase in structural efficiency is 114.36%. The flange thickness of 0.02m and web thickness of 0.015m has the highest structural efficiency at 45.756 and 29.171 respectively. In conclusion, a beam should be able to resist large buckling moment and has a lower self-weight as well in order to has a high structural efficiency.